Unlocking the Private Sector Role in Supporting the Sustainable Multipurpose Forest Management in Riau, Indonesia - Rossita, Annuri; Nurrochmat, Dodik Ridho; Boer, Rizaldi; Santoso, Nyoto; Jaya, I Nengah Surati; Purwawangsa, Handian; Ekayani, Meti; Mutaqin, Faizal; Kautsyar, Muhammad Irsyad (Jurnal Manajemen Hutan Tropika, 2026)
This study aims to discover the private sector’s perspective on the sustainable transition of degraded forestlands, including the transformation of oil palm plantations in forest areas into multipurpose forests, identify current barriers in adopting sustainable multipurpose forest management practices on financing and policy aspects, and explore how the private sector can step up its role in forestland restoration. This study was based on field observations, key informant interviews, focus group discussions (FGDs), and literature reviews. This study aims to navigate a path for policy implementation toward decarbonization, as tenurial conflicts, particularly between oil palm plantations and forest areas, are critical for sustainable forest management in Riau. The private sector's interest in sustainable multipurpose forest management is higher when additional benefits from non-timber forest products (NTFPs) are high. This study also found that the private sector’s desire to support sustainable multipurpose forest management stems from the potential benefits of carbon trading. Regarding the carbon market, most respondents are willing to join when  carbon prices are USD4–6 ton-1 of CO2e. It indicates that the private sector is willing to support the domestic carbon market as regulated under the Minister of Environment and Forestry Regulation 21/2022. While the private sector has complied with most transformative policies and mechanisms, respondents expect further incentives and support, particularly to resolve the forestland conflict.